2016
DOI: 10.1371/journal.pone.0165155
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Distribution of Phlebotomine Sand Flies, and Biotic and Abiotic Factors Related to Their Abundance, in an Urban Area to Which Visceral Leishmaniasis Is Endemic in Corumbá, Brazil

Abstract: The monthly distribution and abundance of sand flies are influenced by both biotic and abiotic factors. The present study aimed to evaluate the seasonal distribution of sand flies and the relation between their abundance and environmental parameters, including vegetation and climate. This study was conducted over a 2-year period (April 2012 to March 2014). Monthly distribution was evaluated through the weekly deployment of CDC light traps in the peridomicile area of 5 residences in an urban area of the municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…GIS has been extensively used for generating risk maps for the vector-borne diseases (Palaniyandi, Anand, Maniyosai, Mariappan, & Das, 2016;Rai & Nathawat, Nathawat, 2017). GIS and following statistical models have been used to clarify the main determinants of leishmaniasis occurrence in various epidemiological foci (Fakhar et al, 2017;Oliveira et al, 2016).…”
mentioning
confidence: 99%
“…GIS has been extensively used for generating risk maps for the vector-borne diseases (Palaniyandi, Anand, Maniyosai, Mariappan, & Das, 2016;Rai & Nathawat, Nathawat, 2017). GIS and following statistical models have been used to clarify the main determinants of leishmaniasis occurrence in various epidemiological foci (Fakhar et al, 2017;Oliveira et al, 2016).…”
mentioning
confidence: 99%
“…cruzi abundance and climatic variables showed no significant statistical association [ 24 , 27 , 59 ]. However, it was observed that the species occurs throughout the year, with population peaks in the months with high temperature [ 21 , 24 , 27 , 59 ]. These previous studies considered both male and female specimens of L .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the geographical distribution of L . cruzi seems to be restricted and limited to Cerrado and Pantanal biomes [ 23 , 24 , 27 29 ]. There are also reports of the presence of L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, engineered bacteria such would be introduced to field endemic sand fly breeding habitats or bait-traps, and thus incorporated into the larval microbiome where the bacteria would persist through adulthood [240,244,245]. Proper evaluation of the sand fly life cycle and seasonal variation in the population would be important to determine when application of the paratransgenic bacteria be administered to the environment [246][247][248][249]. Because the sand fly midgut microbiome is unusually diverse for an insect vector, there are many opportunities to generate a paratransgenic bacterial species that could provide anti-Leishmania properties in the adult female fly.…”
Section: Potential Vector-mediated Biological Control Effortsmentioning
confidence: 99%